Micro- to macro-scale internal structures, diagenesis and petrophysical evolution of injectite networks in the Vocontian Basin (France): Implications for fluid flow. (June 2015) - Ravier, Edouard; Guiraud, Michel; Guillien, Arthur; Vennin, Emmanuelle; Buoncristiani, Jean-François; Portier, Eric
Abstract: This study discusses the characteristics of two Lower Cretaceous injectite networks in the Vocontian Basin (SE France) using combined structural, sedimentary, diagenetic, and petrophysical analyses. Internal structures, at both the macro- and micro-scale, and diagenetic phases characterising these injectite networks have been described. Simultaneously, precementation porosity values were estimated and parameters controlling the geographical distributions of these values were analysed and statistically tested. All of the data were integrated so as to reconstruct the spatial evolution of the porosity from the time of injection to modern times through five major phases. (1) The injection of fluidised sand into hydrofractures combined with high porewater pressure results in high porosity (up to 53%) where injectite thickness and distance to the parent beds exert a primary control. (2) Early deformational imprints, including elutriation structures and cataclastic deformation bands, cause a reduction in the localised porosity. (3) At low burial depths, the intruded sand becomes pervasively cemented by carbonate and is associated with a drastic decrease in porosity (<5%). (4) After lithification, injectites are affected by late tectonic deformations inducing the reopening of fluid conduits, illustrated by the occurrence of carbonate cemented joints. (5) The last phase characterising the porosity evolution is related to the exhumation of both networks, causing an increase in porosity (up to 25%) due to cement dissolution by meteoric fluids. The chronological evolution of the porosity illustrated in this study highlights that injectite networks alternate periods of fluid pathways and fluid barriers, suggesting a strong involvement in petroleum and aqueous fluid flow through time. Highlights: Two Cretaceous deep-marine injectite networks in the Vocontian Basin are studied. Their internal structures and their diagenetic sequences are described. Precementation porosities are measured in injectites and parent beds. Parameters controlling the distribution of precementation porosities at outcrop scale are tested. The evolution of porosity is reconstructed and its implications on fluid flow discussed.